Pemikiran Filsafat Pendidikan Rekonstruksionisme: Implikasi terhadap Pendidikan Karakter dan Pendidikan Moral - Gema Adhari Sutrisno; Siti Nurhidayatul Marati; Herlini Puspika Sari (Jurnal Budi Pekerti Agama Islam, 2025)
Reconstructionism is a school of educational philosophy that aims to reshape society through radical educational reform. Rooted in a critique of progressivism, it emerged as a response to social and economic stagnation and the desire to make education an agent of social change. Its leading figures, such as George Counts and Harold Rugg, inspired by the thought of John Dewey and Theodore Brameld, advocate for an education that is able to deal with global challenges, including moral, social and environmental issues. Reconstructionism argues that education is not only responsible for shaping individuals, but also plays a role in building a just and equal society. The principles of this school emphasize the important role of education in dealing with the global crisis, as well as the need for a relevant curriculum to foster students' character and morals. This school places teachers as agents of change who play an important role in guiding students to face the challenges of the times, as well as designing a curriculum that prioritizes social interests. Thus, reconstructionism emphasizes the importance of education in saving civilization through the formation of character, morality, and a new, more humanist culture.